Compromised Endothelium‐Dependent Hyperpolarization‐Mediated Dilations can be Rescued by NS309 in Obese Zucker Rats. (November 2014) - Tajbakhsh, Negara; Sokoya, Elke M.
Abstract Objective NO and a non‐NO/prostacyclin EDH mechanism are major contributors of vascular tone and cerebral blood flow. However, the effect of metabolic syndrome on EDH‐mediated responses in cerebral vessels remains unknown and may offer another avenue for therapeutic targeting. The purpose of this study was to investigate EDH‐dependent responses in cerebral arteries during metabolic syndrome. Methods EDH‐dependent dilations were assessed in MCAs isolated from nondiabetic obese and lean Zucker rats in the presence and absence of NS309, an activator of SKCa and IKCa channels. IKCa channel expression and activity were assessed by western blotting and pressure myography, respectively. Results EDH‐mediated dilations were significantly attenuated in the obese compared to the lean Zucker rat MCA. Luminal delivery of 1 μM NS309 enhanced EDH‐mediated responses in lean and obese Zucker cerebral vessels. Both dose‐dependent dilations to luminal NS309 and IKCa protein expression in pooled cerebral arteries were comparable between the two groups. Conclusions Our results suggest that pharmacological targeting of IKCa channels can rescue EDH‐mediated dilations in obese Zucker rat MCAs. Compromised EDH‐mediated dilations in obesity are not due to impaired IKCa channel expression or activity.